A geological pressure model for the Browse Basin and the southern Vulcan Sub-Basin, NWS Australia. Issue 1 (1st December 2019) - Heller, Jakob; Shi-Yuan, Toh; Edwards, Alex
Summary: The results presented in this paper draws on a regional pressure analysis of the offshore areas of the Browse Basin and the southern Vulcan Sub-Basin. The presented study focuses on Late Permian to Recent stratigraphy and a new stratigraphic scheme consisting of 11 main sequences has been developed as part of the study. Vp-Rho cross plot analysis conducted for wells in the study area, indicates that undercompaction (disequilibrium compaction) is the main overpressure generating mechanism present. Although no clear deviation from a normal compaction/disequilibrium compaction trend is evident in the analysed wells, densities can be very high at depth with densities up to 2.65 g/cm 3 and above. This indicates that some cementation and possible clay mineral transformations have taken place in the deeper (and older) shales posing a challenge to conventional porosity/effective stress related pore pressure prediction. For the purpose of this study, a model describing (shale) overpressures due to "primary" and "secondary" disequilibrium has been developed. The developed geological pressure model shows an overall good match with shale pressure predictions and/or forms the upper bound of the observed shale pressure/drilling data for the majority of the analysed wells across the study area. The model is particularly useful when planning to drill in areas with few offset wells for calibration and may also form a supplement to pore pressure predictions from seismic velocities away from well control and thereby significantly reduces the risk of encountering unexpected high pressures.